Education Research and Policy: A Commentary on Jabbar and Menashy’s “Economic Imperialism in Education Research: A Conceptual Review” - Don A. Affognon, (Journal of Educational Issues, 2024)
In light of recent suggestions by Jabbar and Menashy that economics has colonized other social sciences and influenced the way policymakers enact education reforms, I examine the question whether economic imperialism warps education policy. For many reasons, I find the hypothesis unrealistic. It ignores that the term “economic imperialism” implies that there is a deliberate or concerted attempt among economists to subjugate other social scientists. It is weakened by the acceptance and enduring application of economic theory in law, psychology, corporate finance, sociology, healthcare, and so on. And it erodes one of the pillars upon which the academy rests: the collaborative production of knowledge which requires interactions and exchanges. I contest the claim that economics has taken over other disciplines and undermined the education reform process. I disagree that an overreliance on economic theory suffuses policymaking, and I find it hard to believe that by focusing primarily on economic outcomes, policymakers disregard other important aims of education. The hypothesis that the preponderance of economics in education policy is attributable to its usefulness is intrinsically realistic and avoids all undue antagonisms.